Predictors of Groin Access Pseudoaneurysm Complication: A 10-Year Institutional Experience. (January 2020) - Naddaf, Abdallah; Williams, Stephen; Hasanadka, Ravishankar; Hood, Douglas B.; Hodgson, Kim J.
Objective: In clinical practice, the incidence of femoral pseudoaneurysms requiring repair is small, but at a tertiary care center, the repair rate is higher due to referrals. We sought to specifically study patients who suffered postcatheterization pseudoaneurysms requiring thrombin injection or operative repair and compare them to our routine transfemoral endovascular patients to identify predictors of clinically significant pseudoaneurysms. The underlying goal would be to identify what makes these patients that develop pseudoaneurysms different. Methods: A search of our billing records for Current Procedural Technology (CPT) codes of these 2 procedures between January 2008 and April 2018 was combined with our institution's Peripheral Vascular Intervention Vascular Quality Initiative database spanning from January 2013 to December 2017. A comparison was then performed between patients who had the outcome of operative intervention for a pseudoaneurysm complication and those who did not, with the goal of elucidating patient demographics and periprocedural factors that would predict pseudoaneurysm formation using univariate and multivariate analyses. Results: There were 77 patients who required thrombin injection or open repair for access-related pseudoaneurysms and 324 patients who did not. Complications occurred more often in patients who were older than 75 (40.2% vs 21.9%; P = .0009), female (57.1% vs 38.6%; P = .003), obese (59.7% vs 33.3%; P < .001), hypertensive (96.1% vs 79.3%; P = .0005), who received a sheath >6F (32.4% vs 13%; P < .0001), intraoperative and postoperative anticoagulation (77.3% vs 32.7% and 52.1% vs 24.2%, respectively; P < .0001), and periprocedural P2Y12 inhibitors (48.7% vs 28%; P = .0005). Less complications were observed in patients who had a closure device used (42.9% vs 8.45%; P < .0001) and protamine reversal (26.5% vs 13.3%; P = .0163). Conclusions: Our findings validate published reports that incriminate a larger sheath size, perioperative anticoagulation, and female gender as increasing the rate of access site complications, with the use of a closure device being protective.